Activation and Migration of Adventitial Fibroblasts Contributes to Vascular Remodeling. Issue 7 (19th February 2018) - Han, Xiaowan; Wu, Aiming; Wang, Jie; Chang, Hong; Zhao, Yizhou; Zhang, Yan; Mao, Yingqiu; Lou, Lixia; Gao, Yonghong; Zhang, Dongmei; Li, Tong; Yang, Tao; et al.
ABSTRACT: The rat carotid artery balloon injury model was used to prove the activation and migration of adventitial fibroblasts. We found that at day 7 after injury, adventitial fibroblasts proliferated, transformed into myofibroblasts under transmission electron microscopy in the model group. Simultaneously, we proved that the adventitial cells migrated to the media and intima on seventh day after injury by directly labeled the adventitial cells by the in vivo gene transfer technique. Moreover, we captured the precise moment when the adventitial fibroblasts migrated from the adventitia to the media through the external elastic plate under transmission electron microscope. This study provides direct evidences that adventitial fibroblasts activate and migrate to the media and intima, then actively take part in revascularization. Anat Rec, 301:1216–1223, 2018. © 2018 Wiley Periodicals, Inc.